Adsorption of cd(ii), ni(ii) and cu(ii) using activated rock melon shell waste : kinetics and equilibrium - Amalina, Roslan (2014)
Heavy metals in wastewater exhibit a global concern of environment due to its toxicity characteristics to many organisms. Adsorption can be used for high separation efficiency of heavy metals in waste water. This method widely used in this industry using different type of adsorbent. The use of low-cost adsorbents has been investigated as a replacement for current costly methods of removing heavy metals from solution. The objective of this research is to investigate the potential of rock melon shell waste as alternative adsorbent to adsorb Cd (II), Ni (II) and Cu (II) ions on aqueous solution. In this research, rock melon shell is used to replace the highly cost adsorbent used in the waste water industry The rock melon shell will be dried, ground and separate by their size through sieve shaker. Then, the rock melon shell powder was activated in the furnace at temperature range 400 ˚C - 650 ˚C. The prepared adsorbent and adsorbate were used for testing the removal effect of the heavy metals by manipulating the parameters of solution pH, contact time and adsorbent dosage. The results were analyzed by using the Atomic Absorption Spectroscopy (AAS). The optimal process conditions were used for kinetic and adsorption equilibrium. The percentage removal of Cd (II), Ni (II) and Cu (II) had been measured and modeled. The percent adsorption of Cd (II), Ni (II) and Cu (II) increased with increased in pH, contact time and adsorbent dosage. However, it tends to achieve equilibrium state once the active sites of the adsorbent are fully occupied. The condition where it gave the highest percentage removal is at 120 minutes contact time, at pH=8 and adsorbent dosage of 0.3g which is exceed 99%. Adsorption of Cd (II), Ni (II) and Cu (II) ions from aqueous solution approved the second-order kinetic yielding good R2 values of 1.00 and k values of 0.0781 to 0.1776